Angela Vergara, Copper workers, international business, and domestic politics in cold war Chile, University Park, PA The Pennsylvania State University Press, 2008 - LAURA BADALONI (H-Industri@)
Angela Vergara, Copper workers, international business, and domestic politics in cold war Chile, University Park, PA The Pennsylvania State University Press, 2008